2008
DOI: 10.1021/ar700192d
|View full text |Cite
|
Sign up to set email alerts
|

The Liquid–Liquid Interface as a Medium To Generate Nanocrystalline Films of Inorganic Materials

Abstract: Unlike the air-water interface, the organic-aqueous (liquid-liquid) interface has not been exploited sufficiently for materials synthesis. In this Account, we demonstrate how ultrathin nanocrystalline films of metals such as gold and silver as well as of inorganic materials such as semiconducting metal chalcogenides (e.g., CdS, CuS, CdSe) and oxides are readily generated at the liquid-liquid interface. What is particularly noteworthy is that single-crystalline films of certain metal chalcogenides are also obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
172
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(178 citation statements)
references
References 36 publications
3
172
0
3
Order By: Relevance
“…In contrast, synthetic chemists generally regard such an interface as an intractable barrier to be circumvented by the use of phase transfer reagents. A small number of studies have explored the use of the water-oil interface to synthesize inorganic nanostructures, materials that have assumed great significance in recent times (Faraday 1857;Brust et al 1994;Rao et al 2005;Fan et al 2007a,b;Rao & Kalyanikutty 2008). In these studies, the use of the interface leads to remarkably simple and straightforward routes to complex solids.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, synthetic chemists generally regard such an interface as an intractable barrier to be circumvented by the use of phase transfer reagents. A small number of studies have explored the use of the water-oil interface to synthesize inorganic nanostructures, materials that have assumed great significance in recent times (Faraday 1857;Brust et al 1994;Rao et al 2005;Fan et al 2007a,b;Rao & Kalyanikutty 2008). In these studies, the use of the interface leads to remarkably simple and straightforward routes to complex solids.…”
Section: Introductionmentioning
confidence: 99%
“…1A), as a consequence of the blocking of the L/L interface and hindering the ion transfer. The role of the standard potential difference between the two redox reactants, as a main driving force of the reaction (1) [12][13][14], the rate of the metal deposition and the morphology of the deposit depend on various factors, the most important being the reactant concentration ratio and the potential difference at the NB/W interface controlled by the partition of common ClO 4 − ions. For gold deposition, the morphology and ordering of the particles can be controlled by a thiol anchoring from both sides of the L/L interface.…”
Section: Resultsmentioning
confidence: 99%
“…Their application ranges from determination of thermodynamic [2,3] and kinetic parameters of ion [4,5] and/or electron transfers [1,6], mechanistic [7] and biomimetic studies of membrane processes [8], to bioelectroanalysis [9,10]. Besides, it has been demonstrated that TFE are an excellent scaffold for studying metal nanoparticle deposition at the L/L interfaces [11], which is a unique environment due to its molecular smoothness [12]. Owing to the pronounced sensitivity of the voltammetric response of TFE to the properties of the liquid interfacial region, the aggregation of nanoparticles can be effectively examined by means of voltammetric techniques [11].…”
Section: Introductionmentioning
confidence: 99%
“…The region in the vicinity of the interface is host to a ra of singular process that govern the transport of ions and direct the structure of the emergent mesostructure. [5][6][7] Advantages of this method include simplicity, low-costs and convenience in that crystalline deposits can be obtained at low temperatures and transferred to a variety of substrates. However, our understanding of the underlying mechanisms are poor.…”
Section: -7mentioning
confidence: 99%
“…Molecular precursor mediated interfacial deposition of nanostructures is one such scheme. A recent revival of interest in this area [5][6][7] has led to materials of topical interest such as thin lms made of pyramidal PbS nanocrystals bound by high energy {331} surfaces, 8 nanorod structures of CdS 9 and Bi 2 S 3 .…”
Section: Introductionmentioning
confidence: 99%